Common themes and challenges in hemophilia care: a multinational perspective. Issue 1 (1st January 2019) - Stoffman, J.; Andersson, N. G.; Branchford, B.; Batt, K.; D'Oiron, R.; Escuriola Ettingshausen, C.; Hart, D. P.; Jiménez Yuste, V.; Kavakli, K.; Mancuso, M. E.; Nogami, K.; Ramírez, C.; et al.
ABSTRACT: Objective : To identify ways that provision of hemophilia care can be maximized at the local level, irrespective of available resources or cultural or geographic challenges. Methods : The SHIELD group used its multinational experience to share examples of local initiatives that have been employed to deliver optimal hemophilia care. Results : The examples were reviewed and categorized into four key themes: guidelines and algorithms for delivery of care; collaboration with patients and allied groups for care and education; registries for the monitoring of treatment and outcomes and health care planning and delivery; and opportunities for personalization of care. These themes were then incorporated into a road map for collaborative care in hemophilia that reflected the contribution of best practice. Discussion : Differing healthcare reimbursement systems, budgetary constraints, and geographical and cultural factors make it difficult for any country to fully deliver ideal care for people with hemophilia. The SHIELD approach for collaborative care provides illustrative examples of how four key themes can be used to optimize hemophilia care in any setting. Abbreviations: AHCDC: Association of Hemophilia Clinic Directors of Canada; AICE: Italian Association of Hemophilia Centres; ATHN: American Thrombosis and Hemostasis Network; EAHAD: European Association for Haemophilia and Allied Disorders; EHC: European Hemophilia Consortium; FIX: Coagulation Factor IX; FVIII: Coagulation Factor VIII; HAL: Haemophilia Activity List; HJHS: Haemophilia Joint Health Score; HTC: Hemophilia Treatment Centre; HTCCNC: Hemophilia Treatment Centre Collaborative Network of China; MASAC: Medical and Scientific Advisory Council; MDT: Multidisciplinary team; NHD: National Haemophilia Database; NHF: National Hemophilia Foundation; PK: Pharmacokinetics; POCUS: Point of care ultrasound; PWH: People with haemophilia; SHIELD: Supporting Hemophilia through International Education, Learning and Development; WFH: World Federation of Hemophilia